Assessment of care quality to patient with acute coronary syndrome in an emergency service - Felipe Gonçalves dos Santos; Cássia Regina Vancini Campanharo; Maria Carolina Barbosa Teixeira Lopes; Meiry Fernanda Pinto Okuno; Ruth Ester Assayag Batista (Universidade Federal de Goias, 2015)
A study aimed to assess quality indicators of the care for patients with suspicion of acute coronary syndrome (ACS) and associate them to discharge, death and, duration of hospitalization. A cross sectional, analytical study of 84 records of patients with ACS suspicion at the emergency service. The association between risk factors and quality indicators of ACS care as: duration of hospitalization, death, recurrence of ischemic events and myocardial revascularization were studied through Spearman's correlations. The duration of hospitalization was significantly smaller for patients with myocardial infarction without ST segment elevation, with a shorter interval between admission and treatment. For patients with myocardial infarction with ST segment elevation, the hospitalization time was significantly shorter when the interval between the risk classification and treatment was shorter. There was no association of quality indicators as recurrence of ischemic events, myocardial revascularization, duration of hospitalization and death.